Implementing a Healthy Lifestyle with Joint Fitness Gymnastics During the Post Covid 19 Period in Banjarsari Village - Ifa Khoiria Ningrum; Olivia Dwi Cahyani (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
Sport is a form of physical activity that is carried out in a planned and structured manner which in its implementation involves repeated body movements to improve physical and spiritual fitness. Sport is an important thing and must be done by the community in the midst of the COVID-19 pandemic because exercise can improve the body's immune system. This community service activity aims to implement a healthy lifestyle in the post-covid 19 period with fitness exercises. The method used is action research with the implementation of this service activity carried out in Banjarsari village, Trucuk sub-district, Bojonegoro Regency through 3 stages, namely: 1) Planning, 2) Implementation, 3) Evaluation. Based on the results of the implementation of community service activities in the form of implementing a healthy lifestyle with fitness exercises on 10, 17, 24 October 2021, it can be concluded that the community is very enthusiastic and enthusiastic about participating in these activities. This can be seen by the seriousness of the community in participating in fitness gymnastics activities.